1998
DOI: 10.1002/(sici)1097-0126(199804)45:4<347::aid-pi940>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of blends of polycarbonate with unmodified and maleic anhydride grafted ABS

Abstract: Blends of polycarbonate/acrylonitrile–butadiene–styrene terpolymer (PC/ABS) and polycarbonate/maleic anhydride grafted ABS (PC/MABS) were prepared over the whole range of compositions using a single‐screw extruder. Tensile, flexural, notched Izod impact properties, and the heat deflection temperature of these blends were determined. Mechanical properties of PC/MABS blends are nearly equal to or higher than, those predicted by the rule of mixtures, whilst those of PC/ABS blends show nearly equal, or negative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 4 publications
4
34
0
Order By: Relevance
“…20 Maleic anhydride grafted ABS have been used as both impact modifier and compatibilizer for polycarbonate (PC)/ABS blends. [26][27][28][29][30] George et al [31][32][33] and Nakason et al 34 reported the effects of maleic modified polypropylene (PP) on the PP/nitrile rubber blends [31][32][33] and PP/maleated natural rubber blends as a compatibilizer. 34 In the studies of PP/clay nanocomposite, Park et al 37 reported the effect of MAH-grafted PP (PP-g-MAH) on the thermal and rheological properties of the PP/clay nanocomposite.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…20 Maleic anhydride grafted ABS have been used as both impact modifier and compatibilizer for polycarbonate (PC)/ABS blends. [26][27][28][29][30] George et al [31][32][33] and Nakason et al 34 reported the effects of maleic modified polypropylene (PP) on the PP/nitrile rubber blends [31][32][33] and PP/maleated natural rubber blends as a compatibilizer. 34 In the studies of PP/clay nanocomposite, Park et al 37 reported the effect of MAH-grafted PP (PP-g-MAH) on the thermal and rheological properties of the PP/clay nanocomposite.…”
Section: Introductionsupporting
confidence: 89%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In the melt blends, maleic anhydride groups can easily react with functional groups of polymers to form block or graft copolymers. These resulting copolymers efficiently reduce the interfacial tension between two polymers, thus, also improve physical and mechanical properties of the blends.…”
Section: Introductionmentioning
confidence: 99%
“…Greco (1996) for a review. A general trend reported in the experimental literature is that under tensile loading of unnotched specimens the ductility (strain at failure) of PC/ABS decreases with increasing ABS content because the ability of neat PC to undergo large strains and ductile neck propagation ("cold drawing") is hampered by the presence of the ABS (e.g., Greco et al 1994;Balakrishnan and Neelakantan 1998). The dependence of the elastic stiffness and the yield stress of PC/ABS on the ABS content is controlled by the amount of (soft) rubber in the ABS since the SAN matrix of the latter is stiffer and has a higher yield stress than PC (e.g., Kurauchi and Ohta 1984;Greco et al 1994;Ishikawa 1995).…”
Section: Introductionsupporting
confidence: 65%
“…The latter was mainly determined by the rubber content, and the maximum toughness was observed at around 15% rubber in the ABS. Similar highly non-monotonous variations of the fracture properties with composition are reported by other researchers (e.g., Lee et al 1992;Balakrishnan and Neelakantan 1998;Inberg 2001). In accordance with the above mentioned behavior of PC/ ABS under unnotched conditions, an enhanced fracture toughness compared to that of neat PC is only observed for sufficiently sharp notches.…”
Section: Introductionmentioning
confidence: 99%
“…The Td of ABS was slightly increased. The compatibility can be increased by the use of Maleic Anhydride-graft -ABS at about 5-10% of ABS -PLA resin [8]. However, we have taken SEM for ABS-PLA (40:60%) compatibilized with Glycerol 2% (1000 magnification) and is shown in Figure 4 which indicates the ABS is Compatible with PLA.…”
Section: Thermal Analysis 341 Differential Scanning Calorimetrymentioning
confidence: 99%